PERANCANGAN PEDOMETER BERBASIS SENSOR ACCELOROMETER ANDROID - Taufik Rahman; Dedy Kurniawan (LPPM Nusa Mandiri, 2017)
With the demands of the wellbeing of in health care. One of the ways we can do is intensifying footsteps. To evaluate activity done, usually, use a pedometer. The presence of censorship accelerometer the cell phone android can be made an application to replace application a pedometer. This application can be used to count the number of steps feet, the distance traveled and also the amounts calories was burning from the doing activities run and walk. In addition, this program also can calculate the value of Body Mass Index (BMI) and Basic Metabolite Rate (BMR). Methods used in build application these are the dead reckoning with Java programming language using Android Development Tool (ADT). Application pedometer this was working, was evident on when testing error less than 5 % of the number of steps.